Oculocutaneous albinism in a wild koala (Phascolarctos cinereus) with unusual renal impairment. Issue 1 (1st March 2021) - Gonzalez‐Astudillo, Viviana; Palmieri, Chiara; Shaw, Stephanie; Allavena, Rachel
Abstract: An albino koala with progressive weight loss was submitted twice to a wildlife clinic. Due to poor prognosis, the koala was euthanised. Relevant histopathology findings include a membranous glomerulopathy and renal ceroid lipofuscinosis. Transmission electron microscopy revealed thickening of the mesangial matrix and glomerular basement membrane and a few dense deposits suggestive of a chronic nephropathy. Albinism in koalas is rare, and this report describes general features of wildlife albinism as well as drawing a comparison to a well‐described amelanotic syndrome in humans that typically results in a severe glomerulopathy due to circulating or in situ immune complexes.